The male gonostylus of the orchid bee genus Euglossa (Apidae: Euglossini) - Ospina-Torres, Rodulfo; Parra-H, Alejandro; Gonzalez, Victor H. (Zootaxa, 2006)
Genital characters remain unexplored in Euglossa and they could be of great value in recognizing species and understanding the phylogeny of the group as in other bee genera. We examined the external morphology of the male gonostylus in 49 species of Euglossa belonging to five subgenera and eight species groups. Unlike the other euglossine genera, the male gonostylus in Euglossa is morphologically diverse. We recognized and illustrated five types of gonostyli that were sometimes consistent within species groups, and might be taxonomically and phylogenetically informative. We hope to draw more attention to and encourage future systematic studies on Euglossa using these genital characters.